2008
DOI: 10.1021/jp8068392
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface/Interfacial Cu2+ Sites in the Photocatalytic Activity of Coupled CuO−TiO2 Nanocomposites

Abstract: Coupled CuO−TiO2 nanocomposite photocatalysts were prepared by a deposition precipitation method and were characterized with a variety of techniques. Electron paramagnetic resonance (EPR) spectroscopy was employed to study the local structures of surface/interfacial Cu2+ sites using Cu2+ as a sensitive paramagnetic probe. The addition of bulk CuO to TiO2 led to decreased photocatalytic efficiency in the degradation of methylene blue. However, doping with a very small amount of CuO (0.1 wt % copper loading) sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
270
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(287 citation statements)
references
References 56 publications
17
270
0
Order By: Relevance
“…The ambiguity over the positions of the conduction and valence bands in CuO (and Cu2O) results in different explanations for the mechanistic aspects of heterojunction systems. For example, Li et al prepared CuO/TiO2 (rutile) nanocomposites by impregnation and subsequent calcination in air [86]. They tested photocatalytic properties of this material using methylene blue as a model compound under UV/vis irradiation.…”
Section: Cuo-tio 2 Heterojunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ambiguity over the positions of the conduction and valence bands in CuO (and Cu2O) results in different explanations for the mechanistic aspects of heterojunction systems. For example, Li et al prepared CuO/TiO2 (rutile) nanocomposites by impregnation and subsequent calcination in air [86]. They tested photocatalytic properties of this material using methylene blue as a model compound under UV/vis irradiation.…”
Section: Cuo-tio 2 Heterojunctionmentioning
confidence: 99%
“…Li et al concluded that efficient electron transfer from the CB of TiO 2 to CuO led to the absence of Ti 3+ (trapped electrons) in CuO-TiO 2 at high CuO loadings. They formulated a hypothesis that the form of CuO (clusters or nanocrystallites) had a significant influence on the type of charge transfer kinetics between TiO 2 and CuO [86].…”
Section: Cuo-tio 2 Heterojunctionmentioning
confidence: 99%
“…4(c) The addition of too high a concentration of CuO x beyond the optimum value would lead to decreased photocatalytic efficiency. It is possibly because of (1) the shading effect of CuO x that reduces the light absorption of TiO 2 and (2) CuO x acting as charge recombination centers at high concentrations (Li et al, 2008a;Irie et al, 2009).…”
Section: Electron Transfer From Tio 2 Cb To Trapping Sitesmentioning
confidence: 99%
“…Transition metal oxides have gained considerable interest recently due to their potential application in solar cells, 1 displays, 2 sensors, 3 and supercapacitors. 4 Among them, copper oxides are nontoxic and the abundant availability of copper makes these oxides a cheap material available for many applications.…”
Section: Introductionmentioning
confidence: 99%